Highly Siderophile Elements distribution, Os-S isotope systematics and U-Pb dating of mafic-ultramafic-hosted massive sulphide deposits (Southern Urals) – Implications on the sources of metals - Tessalina, Svetlana; Belousova, E. (Elsevier Science BV, 2017)
The behaviour of Highly Siderophile Elements (HSEs), including the Platinum Group Elements (PGEs), Re and Au, is still poorly known in hydrothermal systems due to their low concentrations in hydrothermal fluids and related ore deposits. In this work, HSE abundances were determined by fire assay and ICP-MS analyses in the Devonian Dergamysh and Ivanovka massive sulphide deposits from the Southern Urals, Russia. These deposits occur within mafic-ultramafic rocks of the Main Urals Fault suture zone, where the East-European continental unit comes into contact with the Magnitogorsk island arc system. Despite mafic-ultramafic host-rock compositions, the measured Pt and Pd contents are lower than those in island arc-hosted massive sulphide deposits from the same metallogenic province. In Dergamysh massive sulphides, the PGEs and Au positively correlate with Cu, whereas Pt also correlates with Co. For Ivanovka mainly disseminated ores and host rocks, two trends can be observed: (a) low to high PGE at low Au in rocks, with negative Ni-Pd correlation; and (b) both PGE and Au are variable in ores with significant correlation between Au and Pd. The Os-Pb-S isotope systematics in the seafloor Dergamysh hydrothermal system was mainly controlled by mixing of hydrothermal fluid with isotopic signature inherited from mafic host-rocks, and Devonian seawater. A possible additional contribution from more radiogenic Os component was attributed to older Precambrian rocks, which acquired radiogenic Os composition since their formation. Possible presence of such old rocks in serpentinitic melange was evidenced by U-Pb ages of zircons from Dergamysh deposit host rocks, ranging from 3.3 Ga to 507 Ma. These Archaean to Proterozoic zircons are consistent with source from the Volga-Uralia block of the East-European craton, adjacent to the Urals orogenic belt. Light sulphur isotopic composition in Dergamysh ores was attributed to bacterial reduction processes, which was also observed for modern serpentinite-hosted seafloor systems. Disproportionation of magmatic fluid however cannot be completely ruled out.